Usage of Psychophysiological Data as an Improvement in the Context of Software Engineering: A Systematic Mapping Study - Vieira, Roger Denis; Farias, Kleinner (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de Informação, 2020)
A systematic mapping had been developed seeking for answering six research questions regarding using of psychophysiological data in the Software Engineering domain. Employing it was selected 2084 studies from 7 digital databases, reaching a final amount of 27 articles. Mostly of experimental nature, marked by usage of the sensing devices and integrated development environments (IDEs), looking for analysis of developers’ psychophysiological attributes applied to comprehension and debugging of source code. It was not identified as native mechanisms to support psychophysiological data integration and analysis within the integrated development environment.